Respuesta :
solution:
[tex]x^{2}+12x-7=0\\
add 7 to both side of the equation\\
x^{2}-12x=7\\
to creat a trinomial square on the left side of the equation.\\
find a value that is equal to the square of b and the cofficent of x.\\
(\frac{b}{2})^2=(-6)^2\\
add the term to each side of the equation\\
x^2-12x+(-6)^2=7+(-6)\\
x^2-12x+36=43\\
(x-6)^2=43\\
solve the equation for x.\\[/tex][tex]take the square root of each side of the equation to the set up the solution x,\\
(x-6)^2.\frac{1}{2}=\pm \sqrt{43}\\
x-6=\pm \sqrt{43}\\
x=6\pm \sqrt{43}[/tex]
Answer:
x^2+12x+36=7+36
Step-by-step explanation:
I just took the test.
![Ver imagen kaitlynwooley](https://us-static.z-dn.net/files/dc6/106ccb7db00c166808c762c663fc0ace.png)